Essays on household loan-to-value macroprudential policy - Gatt, William (2021)
This thesis is a collection of three papers on the use of the loan-to-value (LTV) ratio as a borrower-based macroprudential policy tool. The first chapter discusses the practical and theoretical development of the LTV ratio as a policy tool over time, as well as reviews the empirical evidence on its general effectiveness in dampening credit growth and its recent specific implementation in two advanced economies, New Zealand and Ireland. The second chapter studies the implications of LTV policy that is implemented asymmetrically over the medium term: a strong tightening response during a boom but a weak unwinding in the bust and recovery phase of the cycle. This is motivated by policymakers' recent statements as well as some empirical evidence. Using numerical simulations I show that this policy is inferior to symmetric policy implementation as it leads to a deeper bust and a more volatile economic environment. In the third chapter, I study the long run distributive effects of the introduction of a macroprudential policy regime which lowers the LTV ratio permanently. I compare the long run effects between economies with two levels of wealth inequality, capturing a range that is representative of several countries in Europe. I show that the policy has a very small long run effect on total wealth inequality, and this is true for the two polar economies. Homeownership falls, with similar dynamics in both economies. While housing wealth inequality increases, the effect is stronger in the economy with lower initial wealth inequality. This is because in the latter economy a greater share of households become borrowing-constrained. Therefore, the same policy can have differential impacts across countries.